2022
DOI: 10.1002/smll.202203231
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Dispersed Cu in Zeolitic Imidazolate Framework Nanoflake Array for Dendrite‐Free Zn Metal Anode

Abstract: Aqueous Zn metal batteries (AZMBs) have been considered as a promising alternative to the existing Li‐ion batteries. Nevertheless, the large‐scale application of the AZMBs is restricted by the dendrite formation and side reactions within the Zn metal anodes (ZMAs) during cycling. Herein, an atomically dispersed Cu in leaf‐like Zn‐coordinated zeolitic imidazolate framework (ZIF‐L) nanoflakes on Ti mesh (CuZIF‐L@TM) as ZMA host is developed. The 3D conductive network formed by the interconnected ZIF‐L nanoflakes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…[1][2][3] The electro-plating-stripping of Zn metal anode shows relatively high reversibility in mild acidic electrolytes, which makes the secondary Zn metal batteries practically possible. [4,5] Nevertheless, the commercialization of secondary Zn batteries is still hindered by two intrinsic issues of the Zn metal anode, i.e. the parasitic hydrogen evolution reaction (HER) and the uncontrolled Zn dendrite growth.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The electro-plating-stripping of Zn metal anode shows relatively high reversibility in mild acidic electrolytes, which makes the secondary Zn metal batteries practically possible. [4,5] Nevertheless, the commercialization of secondary Zn batteries is still hindered by two intrinsic issues of the Zn metal anode, i.e. the parasitic hydrogen evolution reaction (HER) and the uncontrolled Zn dendrite growth.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28] In particular, N-rich zeolitic imidazolate frameworks (ZIFs) have been utilized as ideal precursors for the fabrication of SACs with catalytically active MN x centers. [29][30][31][32][33][34][35][36][37] However, the microporous nature of most ZIFs results in derived SACs with low porosity, which would greatly hinder the mass transfer of reactants and the accessibility of active sites. Recently, we reported a three-dimensional (3D) ordered macroporous ZIF-8 single crystal (SOM-ZIF-8), 38 which can serve as an ideal template/precursor for the construction of SACs with a 3Dordered macroporous (3DOM) structure.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, continuous hydrogen evolution inevitably induces an amount of OH – , ultimately changing the pH value of the electrolyte environment. The OH – can not only combine with Zn 2+ to form ZnO on the surface of Zn but also react with Zn leading to an erosive Zn electrode. For overcoming the above obstacles, many efforts have been applied to design electrolyte and modify Zn anodes. , In terms of electrolyte design, some previous works have been proved that both the high concentration electrolyte and electrolyte additives were effective approaches to obtain stable a Zn anode. In the modification of zinc anode, Zheng et al have reported that a low mismatch lattice between graphene and metallic zinc plays a crucial role in uniforming zinc deposition . Furthermore, introducing buffer coating has been known as a more effective strategy to suppress the Zn dendrite, improving the performance of the Zn anode. Kang et al rationally constructed a porous CaCO 3 layer on the Zn foil to even out Zn 2+ fluxing, which can effectively moderate the deposition position of Zn 2+ and lead to a dendrite-free anode .…”
Section: Introductionmentioning
confidence: 99%